2007
DOI: 10.1002/chem.200601003
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Behavior of a Metal‐Organic Framework (MOF)

Abstract: Upon light excitation MOF-5 behaves as a semiconductor and undergoes charge separation (electrons and holes) decaying in the microsecond time scale. The actual conduction band energy value was estimated to be 0.2 V versus NHE with a band gap of 3.4 eV. Photoinduced electron transfer processes to viologen generates the corresponding viologen radical cation, while holes of MOF-5 oxidizes N,N,N',N'-tetramethyl-p-phenylenediamine. One application investigated for MOF-5 as a semiconductor has been the shape-selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
504
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 844 publications
(544 citation statements)
references
References 24 publications
20
504
1
4
Order By: Relevance
“…Previous studies found that linker modification were beneficial for the UV‐light active MOF photocatalysts based on titania or zirconia clusters, due to the ligand‐to‐metal charge transfer (LMCT) mechanism 32, 33. The PL has been proved as a powerful technique to study the LMCT mechanism in MOFs 32, 43. For NH 2 –MIL‐88B (Fe), there also exists the electron transfer from the BDC–NH 2 organic linker to Fe 3 ‐μ 3 ‐oxo clusters, and such electron‐transfer process was studied by PL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that linker modification were beneficial for the UV‐light active MOF photocatalysts based on titania or zirconia clusters, due to the ligand‐to‐metal charge transfer (LMCT) mechanism 32, 33. The PL has been proved as a powerful technique to study the LMCT mechanism in MOFs 32, 43. For NH 2 –MIL‐88B (Fe), there also exists the electron transfer from the BDC–NH 2 organic linker to Fe 3 ‐μ 3 ‐oxo clusters, and such electron‐transfer process was studied by PL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, metal-organic frameworks (MOFs) with outstanding characteristics have attracted tremendous attention as catalysts or catalyst carriers for photocatalytic water splitting in the past few years [29][30][31]. Although there are still some limitations, the opportunities for MOFs as heterogeneous catalysts are very encouraging [32][33][34][35] because MOFs as a new class of porous material have exciting characteristics, such as high surface areas, crystalline open structures, tunable pore size, and functionality. Particularly, the high specific surface area of MOFs may provide more attachment points for a cocatalyst, in which it could create more active sites and make better contact with reactants.…”
Section: Introductionmentioning
confidence: 99%
“…(Online version in colour. ) mediocre structural stability, wide band gaps and feature poor semiconducting properties, with the exception of the ZnO-based MOF-5 and related compounds (Alvaro et al 2007). In contrast to MOFs, hybrid systems containing higher dimensionality in the inorganic networks, introducing the possibility of novel anisotropic electronic, magnetic and optical effects, with improved thermal and chemical stability, have been relatively neglected; two notable exceptions being experimental work from the groups of Li (Zhang et al 2006;Guo et al 2009;Huang et al 2009) and Maggard (Lin & Maggard 2007Lin et al 2009).…”
Section: Introductionmentioning
confidence: 99%